Low Carbon Education: How is Its Existence in Schools? - Annisa Nurramadhani; Riandi Riandi; Anna Permanasari; Irma Rahma Suwarma (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
This research aims to investigate how is the teacher’s understanding of Low Carbon Education (LCE) concept explicate and implicit, the implementation of environmental education that has already implemented, implementation of the adiwiyata program. This research used a survey method of the 58 teachers of elementary school, junior high school, and senior high school) in Kota Bogor. The instrument that is used is 76 questions included in the questionnaire about Low Carbon Education (LCE) comprehension, implementation in classes, and implementation of environmental education and green school program. Data are also taken by interviewing the teachers who have already done the environmental education teaching and learning in the classes and also the teachers who had already done the green school program (Adiwiyata). low carbon education terms have not been familiar explicitly in teachers at schools and also there is not a specific subject or topic in Indonesian curricula, while the low carbon education topics have already been integrated into Environmental learning which has been implemented in Indonesian curricula. The implementation of environmental learning at schools has in the good category, either pertaining with low carbon education concept or general. Research results is the implementation of environmental teaching materials also has already in good category. Besides that, the environmental practice pertaining low carbon education has been organized by the government for instance green school concept that led to Adiwiyata program for schools. Teacher understanding about that program has in great value which relate to teachers’ attitude toward environment during and after that program.